Not Just Content: Piloting On-Demand Learning through Participant-Centered Instructional Design - Giri, Prakash Chandra (NPRC Journal of Multidisciplinary Research, 2025)
The rising demand for developing and piloting on-demand courses in various institutions show a transformation towards flexible, accessible and innovative education practices. As various institutions adopt and adapt this on-demand model to implement the content and documents, the true effectiveness of these courses depends on effective instructional design and full engagement of the learners. This research study explores creative and innovative ideas for developing and piloting on-demand courses that move beyond just telling the content or passive delivery. Grounded in constructivist learning theory and a phenomenological approach, the study applies both qualitative and quantitative feedback from the pilot participants , analyzed through the thematic and triangulated approach. The results highlight key pedagogical and technological insights for effective LMS application such as launching the live events for orientation and recaping the lessons, showing the content with clear instructions not just telling the content, development of organized content, engaging with discussion prompt questions on the LMS, regular communications, tech supports and course updates, exposure of extra bonus materials, right way of prompting AI tools, focus on diversified and inclusiveness of course moderators and learners. Guided by the ADDIE model, the research reveals a practical framework from the planning step to piloting stage of the course development journey. The study concludes with actionable and practical recommendations for policymakers, instructional designers, curriculum developers, teachers and concerned stakeholders to enhance content quality and implement effective on demand learning environment ensuring showing and engaging the participants rather than merely telling the content.